Regional Differences in Sympathetic Nerve Activity Are Generated by Multiple Arterial Baroreflex Loops Arranged in Parallel - Miki, Kenju; Ikegame, Shizuka; Yoshimoto, Misa (Frontiers in Physiology, 2022)
In this review, by evaluating the responses during freezing, rapid eye movement (REM) sleep, and treadmill exercise, we discuss how multiple baroreflex loops arranged in parallel act on different organs to modulate sympathetic nerve activity (SNA) in a region-specific and coordinated manner throughout the body. During freezing behaviors, arterial pressure (AP) remains unchanged, heart rate (HR) persistently decreases, renal SNA (RSNA) increases, and lumbar SNA (LSNA) remains unchanged. The baroreflex curve for RSNA shifts upward; that for LSNA remains unchanged; and that for HR shifts to the left. These region-specific changes in baroreflex curves are responsible for the region-specific changes in RSNA, LSNA, and HR during freezing. The decreased HR could allow the heart to conserve energy, which is offset by the increased RSNA caused by decreased vascular conductance, resulting in an unchanged AP. In contrast, the unchanged LSNA leaves the muscles in readiness for fight or flight. During REM sleep, AP increases, RSNA and HR decrease, while LSNA is elevated. The baroreflex curve for RSNA during REM sleep is vertically compressed in comparison with that during non-REM sleep. Cerebral blood flow is elevated while cardiac output is decreased during REM sleep. To address this situation, the brain activates the LSNA selectively, causing muscle vasoconstriction, which overcomes vasodilation of the kidneys as a result of the decreased RSNA and cardiac output. Accordingly, AP can be maintained during REM sleep. During treadmill exercise, AP, HR, and RSNA increase simultaneously. The baroreflex curve for RSNA shifts right-upward with the increased feedback gain, allowing maintenance of a stable AP with significant fluctuations in the vascular conductance of working muscles. Thus, the central nervous system may employ behavior-specific scenarios for modulating baroreflex loops for differential control of SNA, changing the SNA in a region-specific and coordinated manner, and then optimizing circulatory regulation corresponding to different behaviors.